Determinants of Productivity: A Conceptual Review of Economic and Social Factors (Journal of Business Management and Accounting, 2018)
Welfare improvement is always a key and one of the major objectives of many nations. One of the most important ways of improving societal welfare is through productivity improvements hence various studies have been conducted in relation to this topic. in addition to the current developments in this area of research, this paper attempts to provide in-depth review of previous studies on the determinants of productivity with the aim of identifying both economic and social factors that affect the level of productivity. The paper shows that previous studies on the determinants of productivity are of different folds (on a different basis). The basis of the previous studies includes â€“ that of economic factors and social factors â€“that of statistical method of analysis and non-statistical method of analysis, some studies are based on tangible â€œgoodsâ€ while some are based on intangible â€œservicesâ€, some factors influence productivity positively while some negatively. Even though, the positive and negative effects of some variables are recognized to be non-mutually exclusive as the same variable might have both positive and negative influence on productivity in two different studies or countries due to the existence of discrepancy of some socio-economic conditions, technological strength and factor intensity among countries, areas of studies and organizations. Also, few studies exist on the determinant of productivity in the service sector compared with those in the goods sector. This paper suggests more empirical studies to be conducted in different countries, organizations and areas of studies especially, on the service sector productivity, as generalizations without empirical studies could be inconclusive and the effects of the determinants may be understated or overstated.